Bladder Perivascular Epithelioid Cell Tumor (PEComa): A Case Report and Literature Review. Issue 2 (April 2015) - Sarti, Alessandra; Rubilotta, Emanuele; Balzarro, Matteo; Cerruto, Maria Angela; Brunelli, Matteo; Artibani, Walter
Introduction: Perivascular epithelioid cell tumors (PEComa) are a very uncommon mesenchymal cancer with uncertain malignant potential. Materials and Methods: A computerized research on Pub Med was performed regarding bladder PEComa. We evaluated the literature cases and described a case of bladder PEComa. Results: PEComa of the bladder is a very rare neoplasm and only 15 cases have been reported so far. Conclusions: Bladder PEComa involves young subjects of both genders, mostly under 40 years of age. Surgical treatment (partial or radical cystectomy) is the most common management. A long-term follow-up and larger series are required to better understand the best clinical approach to bladder PEComa.